Does relationship learning lead to relationship value? A cross‐national supply chain investigation - Cheung, Mee‐Shew; Myers, Matthew B.; Mentzer, John T. (Journal of Operations Management, 2010)
In global business‐to‐business markets, shared resources between buyers and suppliers often result in competitive advantages and enhanced relationships between firms. Unfortunately, there is a paucity of research regarding learning capabilities between business partners in a cross‐border setting. This study takes the approach to integrate customer value literature into interorganizational learning theory and adopts the often‐neglected theoretical perspective of transaction value by contextualizing inter‐firm collaboration in terms of relationship learning and value co‐creation viewed by both the buyers and sellers in one single study. Through the development of a conceptual framework that examines how global environmental and inter‐organizational conditions influence learning capabilities, the study investigates how relationship learning influences relationship value for both supplying and buying firms. Using a survey of 126 cross‐border dyads in the industrial chemical, packaging, consumer durable, and apparel industries, the authors show how relationship learning is valued by both buyers and suppliers, and how it is critical when viewing the “supplier as a customer.” The results indicate the strategic nature of relationship learning in maintaining cross‐border business‐to‐business relationships. Simultaneously, the findings provide evidence that cultural distance is not a significant influence on the firm's propensity to share knowledge with its global partners. It helps advance our understanding of the significance of cultural‐pollination in the era of globalization.